Studi Literatur: Analisis Kecemasan Siswa Pada Pembelajaran Matematika - Nur Laily; Andika Setyo Budi Lestari (Ar-Riyadhiyyat: Journal of Mathematics Education, 2024)
This research aims to investigate literature related to the causes of anxiety in students, delineating the factors that trigger anxiety through data analysis. Employing the Systematic Literature Review (SLR) method with a qualitative approach, the study collected data by searching articles on Google Scholar and Sinta-indexed journals. Out of 100 relevant articles, 23 were selected based on matching criteria. The chosen articles span the publication period from 2017 to 2023 to ensure the freshness and accuracy of the data. The literature review results indicate that the causes of student anxiety can be categorized into personality, intellectual, and social environmental factors. Physiological aspects were also identified as elements influencing student anxiety.